PENGARUH DIFFUSER PADA FLENS ISAP DAN LOCK NUT IMPELLER BERBENTUK TIRUS TERHADAP KARAKTERISTIK POMPA SENTRIFUGAL - M. A., Bramantya; -, Sugiyono; Doni, Rama (Jurnal Energi Dan Manufaktur; Vol 2, No.2 Desember 2007, 2012)
Centrifugal pump is a widely used pump in daily application related to its wide range of head and capacity. In recent years, a number of researches have done considerable work on the improvement of characteristic and performance of centrifugal pumps. This paper explained result of the experiment on the effect of diffuser and haggard lock nut impeller toward to characteristic and performance of the centrifugal pump. Type of the modified pump was GRUNDFOS NF 13-18 no. 9199756 with water 27OC as working fluids. The result showed that the total head and efficiency of the modified pumps was well improved.
Keywords: Centrifugal pump, diffuser, lock nut, head and efficiency